Analysis of Problem-Solving Behavior of Senior High School Students - Hafizatunnisa; Harisman, Yulyanti; Armiati; Amiruddin, Mohd Hasril (Mathematics Education Journal, 2024)
Problem solving behavior focuses on how students process to solve problems, while problem solving ability is a student's ability to solve problems. Problem solving behavior can identify students' problems in solving mathematical problems, so that students' mathematical problem solving abilities are achieved as expected. Therefore, it is important for students to develop their problem-solving behaviors. By paying attention to problem solving behavior, teachers can discover students' obstacles in solving problems. The study aims to describe the problem solving behavior of students with low, medium and high ability levels. The subjects of the study were first-year senior high school students. The students were given mathematical problem-solving questions and then interviewed. Based on the interview transcripts, the students were grouped based on the problem solving behavior rubric. However, a new category of problem solving behavior, i.e., semi-routine, was proposed because the existing behavior categories did not fully represent the observed problem solving behaviors. The results of this study showed that problem solving behaviors are categorized into apathetic, semi-routine, routine, semi-sophisticated, and sophisticated. Aspects of problem solving behaviors are knowledge ownership, control, beliefs, and affective. By improving students' problem-solving behavior, it is expected that students' mathematical problem solving abilities will also improve.